Antibody Responses against Enterovirus Proteases are Potential Markers for an Acute Infection - Saarinen NVV; Stone VM; Hankaniemi MM; Mazur MA; Vuorinen T; Flodstrom-Tullberg M; Hyoty H; Hytonen VP; Laitinen OH (MDPI, 2022)
Background: Enteroviruses are a group of common non-enveloped RNA viruses that cause symptoms ranging from mild respiratory infections to paralysis. Due to the abundance of enterovirus infections it is hard to distinguish between on-going and previous infections using immunological assays unless the IgM fraction is studied. Methods: In this study we show using Indirect ELISA and capture IgM ELISA that an IgG antibody response against the nonstructural enteroviral proteins 2A and 3C can be used to distinguish between IgM positive (n = 22) and IgM negative (n = 20) human patients with 83% accuracy and a diagnostic odds ratio of 30. Using a mouse model, we establish that the antibody response to the proteases is short-lived compared to the antibody response to the structural proteins in. As such, the protease antibody response serves as a potential marker for an acute infection. Conclusions: Antibody responses against enterovirus proteases are shorter-lived than against structural proteins and can differentiate between IgM positive and negative patients, and therefore they are a potential marker for acute infections.